Web-based problem-based collaborative learning for converted muslim in learning Islamic knowledge - Nurul Fatihah Sahidan; Nazrul Azha Mohamed Shaari; Hayati Abd Rahman (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Web-based collaborative learning is well accepted learning methods since it provides flexibilities not only in term of learners’ interaction but also its timeliness learning materials. Even though there are many websites offer learning materials for Muslims generally but for new converted Muslims getting authentic materials and proper guidance are complicated. Hence, a web-based problem-based collaborative learning is proposed. This method integrates an elected virtual instructor to facilitate and support the new converted Muslims’ cognitive and emotional activities, develop their confidence of resolving and dealing with problems they are facing. This paper relates and analyzes the problem-based collaborative learning in terms of the functionality and user acceptance. Based on a survey conducted, it shows that 85% of the respondents found the system very useful and easy to use while 80%found that the system met their requirements. This system hypothetically able to help, and ease new converted Muslims in exploring Islamic authentic knowledge by using problem-based technique in web-based collaborative learning.